Contrôle microbiologique des aliments dans certains restaurants collectifs de la wilaya de Mostaganem - BELGHALEM, Rachida (My University, 2019)
In this work, we carried out a microbiological control of foods from some collective restaurants from different areas in Mostaganem: "Ziane Mohamed" primary school in Ouled Boughalem, "Bouaissi Mohamed" university campus and the cafeteria of the university (Abdelhamid ibn badis) of Mostaganem ( ITA). The results of the study have shown an absence of faecal and total coliforms, of Staphylococcus aureus and Salmonella in all studied foods (dates, cachir, soup and cake). The dates and soup samples taken from a meal served at the primary school, presented a good hygienic quality. The sample of the cachir taken from the university campus restaurant presented a total number of mesophiles of 166 103 CFU / ml. The number of total mesophiles was around 262.72 103 CFU / ml for the madeleine. The number of yeast colonies calculated was 69.09 104 CFU / ml for coffee and 232.72 104 CFU / ml for the madeleine. The result of the inquiry carried out at the archives of the Direction of Health and Population (DSP) of Mostaganem, showed that 263 cases of collective food poisoning were recorded during the year 2017 and 270 cases during the year 2018.
Keywords: Food poisoning; Collective restaurant; Microbiological control; Pathogens